Clinical spectrum and predictors of mortality in critically ill pediatric patients: a retrospective study in a referral pediatric intensive care unit in Peru - Domínguez-Rojas, Jesús (2026)
Introduction: Pediatric intensive care units (PICUs) are essential services in the management and treatment of critically ill children; however, mortality rates remain very high in these services in low- and middle-income countries. Objective: To describe the clinical characteristics of patients admitted to the PICU of a referral hospital in Peru and to determine the factors related to mortality. Methods: A retrospective observational study with time-to-event analysis was conducted in the PICU of a tertiary hospital, including patients aged 0 to 17 years who were admitted between July 2022 and July 2023. Patients who stayed in the PICU for less than 24 hours and those with missing information were excluded. Various sociodemographic and clinical variables were analyzed. A bivariate analysis (chi-square, Student's t-test) and multivariate logistic regression were performed to determine predictors of mortality, and a Kaplan-Meier survival analysis was performed. Results: A total of 503 patients were included (53.1% male; median age 28 months). The main causes of admission were postoperative status (32.8%) and acute respiratory failure (25.2%). Invasive mechanical ventilation was required in 76.5% of patients. The mortality rate was 9.94%. In the multivariate regression analysis, mechanical ventilation (ORaj: 2.41; 95% CI: 1.01–5.77; p=0.047) and healthcare-associated infections (HCAIs) (ORaj: 3.16; 95% CI: 1.28–7.81; p=0.012) were identified as independent predictors of mortality. Survival analysis showed that most deaths occurred between days 7 and 10. Conclusion: Invasive mechanical ventilation and HAIs were independent predictors of mortality in this PICU. Early detection of high severity and strict control of nosocomial infections are recommended.